STRATEGIC MANAGEMENT OF THE BERAU DISTRICT GOVERNMENT IN RESPONSE TO THE IMPACT OF THE ISSUANCE OF THE MINERAL AND COAL POLICY ON COMMUNITY WELFARE - Benni Eka Nugraha Hutauruk; Utang Suwaryo; Dede Sri Kartini (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
Strategic management in government is a systematic process of formulating, implementing, and evaluating key decisions taken by the government to achieve its strategic objectives. These objectives may include improving people's welfare, developing infrastructure, reforming the bureaucracy, or achieving other long-term visions. This research uses a qualitative approach using descriptive methods to obtain an in-depth understanding of the Strategic Management of the Berau Regency Government in responding to the impact of the issuance of Mineral and Coal, the Undang-Undang No. 3 Tahun 2020 on community welfare from 2020 to 2022 in the form of public policy. The sources of information in this research are Berau Regency DPMPTSP employees and Berau Regency DPRD members. Information collection was conducted through interviews, observation and documentation. The results of this study indicate that the Strategic Management carried out by the Berau district government through the Berau DPMPTSP office and the Berau district DPRD has not run optimally. This is because the DPMTSP Office as the executive in the government and the DPRD of Berau Regency as the legislative body of the government in Berau Regency are not given enough space and authority in the management of natural resources in the region, especially in terms of mining, this is caused by regulations from the central government that limit the authority and involvement of local governments in the management of mining and mineral natural resources in Berau Regency.